Notification of Effectiveness of Partial Distribution of the General Reserve Attributed to Windfall Gold Sale Profits. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
On February 24, 2012, the Executive Board approved a partial distribution of the general reserve equivalent to SDR 700 million attributed to part of the gold sales windfall profits to all members in proportion to their quotas.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Equivalent To SDR; Lending Capacity; Notification Of Effectiveness; PP; Windfall Gold Sale Profit; Afghanistan, Islamic Republic of